PERLINDUNGAN HUKUM TERHADAP PEMEGANG POLISTERKAIT KETERLAMBATAN PEMBAYARAN KLAIM ASURANSI JIWA( Studi Putusan Nomor 182/Pdt.G/2020/PN Yyk ) - Muhammad Juan Pratama (2023)
Disputes regarding insurance may arise from an agreement or insurance closure, especially in the insurance claim process such as the insured's obligations and rights if there is a problem in getting insurance claim reimbursement such as delays in paying claims for the insurance. This study aims to find out how legal protection is for policyholders regarding delays in disbursing life insurance claims and how accountability for violations by the Life Insurance Company with Bumiputera 1912 applies to policyholders regarding delays in disbursing life insurance claims based on Study Decision Number 182/Pdt.G/2020/ PN Yyk. The type of research used in this writing is normative juridical research. This research will use a statutory approach (statute approach), namely an approach by looking at standardization in all laws and regulations that affect these problems (legal issues) in this case related to insurance. The results of this study indicate that legal protection related to late payment of claims can refer to default of an agreement and can also be classified as an unlawful act that can be used by policyholders to demand responsibility from the perpetrator in accordance with the provisions in article 1365 of the Civil Code.